Pengaruh Motivasi, Disiplin, dan Stres Kerja terhadap Kinerja Karyawan Pt. Batam Bintan Telekomunikasi Batam - Ngaliman, Ngaliman; Juniastito, Raynaldi; Yanti, Sri (Universitas Batam, 2019)
This study aims to examine and analyze the effect of motivation, discipline and work stress on employee performance at PT. Batam Bintan Telekomunikasi. Data was collected through questionnaires distributed to 40 employees at PT. Batam Bintan Telekomunikasi. The analysis in this study uses the SPSS version 24 program. The data testing technique used is validation test and reliability test with Cronbach Alpha. Classical assumption tests and multiple regression analyses were conducted to test and prove the research hypothesis. The results of the analysis prove that Motivation (X1) has a positive effect on employee perfomance with a t-count of 6,281 and a significance value of 0.010 which is smaller than 0.05. There is a positive and significant effect of discipline (X2) on employees performance. With a t-count value of 5,490 and a significance value of 0.000, it is smaller than 0.05. There is a postitive and significant effect on work stres (X3) on employees performance. With a t-count value of 3,689 and a significance value of 0.018 it is smaller than 0.05. Simultaneously the motivation, discipline, and work stress have a positive and significant effect on employees performance with a calculated F value of 35,638 and a significance value of 0.000 less than 0.05. It can be concluded that motivation, discipline, work stress a positive and significant effect on employees performance.. From the results of the analysis, it can be seen that employees perfomance is influenced by motivation, discipline, work stress of 0,748 (74,8%), while the remaining 25,2% is influenced by other factors not examined in this study.